(untitled) (Historia, 2021)
The breadth of themes that Terence Ranger has helped pioneer is as impressive as the influence of his scholarship is trans-national. The scope of his interventions ranges from urban to rural history, from political and social history and biography to religion, spirituality and culture to the environment, human rights, and wars. Ranger’s scholarship, especially on African nationalism, is not uncontested but research on the above themes has flourished since his pioneering work. Some may appear to have been “left behind” by recent intellectual pathways, but his vision was also to keep up with or pre-empt many cultural turns. Those fields such as political history, which he soon mastered and which some now see as old-fashioned, have suffered neglect too soon to allow their full reconsideration. Advances in the history of culture, gender and the environment have been vital in improving historical perception, but focus on merely one or the other should not blind us to gaping holes remaining in intellectual and regional history; indeed, their very interconnectedness can help extend the frontiers of knowledge. In this regard, Ranger’s injunction for Zimbabwean history, that “nationalism as a movement, or set of movements, and as an ideology ... still requires a great deal of rigorous historical questioning”, remains as relevant today for South Africa.